2022
DOI: 10.1039/d2lc00416j
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-laden droplet size prediction in a flow-focusing microchannel: a data-driven approach

Abstract: The control of droplet formation and size using microfluidic devices is a critical operation for both laboratory and industrial applications, e.g. in micro-dosage. Surfactants can be added to improve the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Resampled latent variables z ′ can be characterized by a normal distribution with mean μ and variance σ denoted as ( μ , σ 2 ), with ε sampled from a Gaussian distribution asTo sum up, the total loss function of VAE 56 presents as = MSE ( x , x̂ ) + KLD ( q ( z|x )‖ p ( z|x ))VAE can be used not only like AEs for dimensionality reduction, but also to generate “consistent” data that are different from inputs because of their latent state representation. 29 Here, by ‘consistent’, we refer to the generated data whose statistical properties mimic those of the original dataset. However, it is also an unsupervised learning method and cannot handle condition-specific samples 57 ( e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Resampled latent variables z ′ can be characterized by a normal distribution with mean μ and variance σ denoted as ( μ , σ 2 ), with ε sampled from a Gaussian distribution asTo sum up, the total loss function of VAE 56 presents as = MSE ( x , x̂ ) + KLD ( q ( z|x )‖ p ( z|x ))VAE can be used not only like AEs for dimensionality reduction, but also to generate “consistent” data that are different from inputs because of their latent state representation. 29 Here, by ‘consistent’, we refer to the generated data whose statistical properties mimic those of the original dataset. However, it is also an unsupervised learning method and cannot handle condition-specific samples 57 ( e.g.…”
Section: Methodsmentioning
confidence: 99%
“…86 In addition, other parameters, including cross-junction tilt angles, flow rates, and surfactant concentration, can also be correlated to the droplet size, and multiple droplet properties other than droplet sizes, such as generation frequency and flow regime, can be accurately predicted. [87][88][89] 90,91 To further increase the model training efficiency, Siemenn et al designed a Bayesian optimization and computer vision feedback loop to quickly discover the control parameters. 92 A full optimization procedure can be completed using 60 samples within 2.3 h. Moreover, Wang et al demonstrated that experimental/numerical data from previous publications can also be used as training data, thus significantly increasing the training efficiency and prediction accuracy.…”
Section: Prediction Of Droplet Propertiesmentioning
confidence: 99%
“…86 In addition, other parameters, including cross-junction tilt angles, flow rates, and surfactant concentration, can also be correlated to the droplet size, and multiple droplet properties other than droplet sizes, such as generation frequency and flow regime, can be accurately predicted. 87–89 To speed up the droplet size measurement, Zhang et al developed a mask R-CNN model for feature extraction and data acquisition. 90,91 To further increase the model training efficiency, Siemenn et al designed a Bayesian optimization and computer vision feedback loop to quickly discover the control parameters.…”
Section: Ai In Droplet Generationmentioning
confidence: 99%
“…
Figure 3.Effect of TX100 concentration on dimensionless drop ( a ) diameter () and ( b ) formation time () using HSI, PIV, CFD and the Bayesian regularised artificial neural network (BRANN) model from Chagot et al. (2022).
…”
Section: Numerical Formulation Scaling and Validationmentioning
confidence: 99%
“…Moreover, a prediction of the drop size was obtained by using a data-driven model (Chagot et al. 2022). As discussed by Kalli et al.…”
Section: Numerical Formulation Scaling and Validationmentioning
confidence: 99%